Arranjos de polimorfismos de ncleotídeo Único (SNPa) e sequenciamento de nova geração (NGS) na avaliação e detecção de anormalidades genético-moleculares na leucemia mieloide aguda (LMA) - Noronha, Thiago Rodrigo de [UNIFESP] (2017)
Introduction: Acute myeloid leukemia (AML) is the most frequent leukemia in adults and results from somatic genetic lesions on hematopoietic progenitor cells that modify the normal life cycle of cells. The karyotype identifies alterations that support diagnosis, prognosis, treatment option and disease monitoring. However, some cases are normal. Hence, the incorporation of new tests becomes necessary to contemplate all of the genetic alterations. Single nucleotide polymorphism array (SNPa) method, also referred to as molecular karyotyping, is a sensitive technology used to perform high-resolution genome-wide DNA copy number analysis and to detect segmental regions of homozygosity, known as uniparental disomy. Next generation sequencing (NGS) is a methodology that allows simultaneous sequencing of several genes related to the disease. Objectives: Investigate the genetic alterations in patients with AML, at the diagnosis, using the SNPa and NGS methods, in order to evaluate the diagnostic gain of applying these technologies to the clinical routine analysis. Material and methods: Bone marrow samples from 49 cases of AML patients, at diagnosis, were evaluated by karyotype, SNPa and NGS. Results: Karyotype: 15 changed, 20 normal and 14 without metaphase. SNPa: 26 changed and 23 normal. NGS: 37 changed and 12 without detected mutations. The most frequent mutations were in the genes DNMT3A, IDH2, NRAS, FLT3-ITD, TET2, NPM1 e IDH1. Eighteen patients had the prognosis modified, four to favorable and fourteen to poor. Seventeen patients had an unknown or inconclusive integrated prognosis. Conclusion: The SNPa and NGS allowed amplify the detection of genetic alterations in AML in relation to the habitual methods. In summary, these results sustain the use of SNPa and NGS as important tools for AML patients, since offers insights into the molecular pathogenesis, indicating that the prognosis could be further stratified by different mutation combinations. All patients could be reclassified based on genomic status and eighteen had their prognosis modified.